Popular consultation for the FTA? - Ortiz García, Pablo (2016)
By assuming a legal point of view, this article argues that the US-Andean Free Trade Agreement should not be approved by a popular referendum. According to legal doctrines and concepts, the free trade agreement is an international treaty; therefore, the people are not entitled to decide whether or not it should be approved. It is also posited that a popular referendum could become very problematic due to factors related to the educational levels of the Ecuadorian population and the political uses of the consultation.